القيم التربوية والخصائص الفنية في مسرح الطفل الجزائري مسرحية صانعة الأحلام السعيدة لسلمان بومعزة أنموذجا - بوجلخة, فضيلة; قروي, حليمة; ميسة, مطيرة; شكيمة, سهيلة (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة البحثية إلى تسليط الضوء على أهم القيم التربوية والخصائص الفنية في مسرح الطفل الجزائري (مسرحية صانعة الأحلام السعيدة أنموذجا) كونه أقرب الفنون الأدبية للطفل، ولهذا يستخدم لأداء أغراض عديدة على حسب الفئة العمرية. تناولنا في بحثنا هذا فصلين، فصل نظري وفصل تطبيقي توصلنا من خلالهما الى عدة نتائج أهمها: إن مسرح الطفل يساهم في تعزيز القيم الأخلاقية والتربوية مثل: الصدق، التعاون، احترام الآخرين والعمل الجماعي.... إن مسرح الطفل يعمل بكل عناصر بنائه الدرامي من فكرة وشخصيات ,وحوار وصراع ولغة وأسلوب, ومكان وزمان بشكل متكامل، ليبث في نفس الطفل أهم القيم الإيجابية المرغوبة، ويخلق له هوية ثقافية خاصة تتناسب مع ثقافة المجتمع. The aim of this research study is to shed light on the most important educational values and artistic characteristics in Algerian children’s theater (the play The Maker of Sweet Dreams as an example), as it is the closest literary art to children, and for this reason it is used to perform many purposes according to the age group. In this research, we covered two chapters, a theoretical chapter and an applied chapter, through which we reached several results, the most important of which are: Children's theater contributes to strengthening moral and educational values such as: honesty, cooperation, respect for others and teamwork.... Children's theater works with all the elements of its dramatic structure, including ideas, characters, dialogue, conflict, language, style, place and time, in an integrated manner, to instill in the child the most important positive values desired, and to create for him a special cultural identity that is compatible with the culture of society.
أدب جديث ومعاصر
Keywords: children's theatre_educational values_artistic characteristics.; مسرح الطفل_القيم التربوية_الخصائص الفنية.